THE EFFECTIVENESS OF TPS MIND MAPPING STRATEGY AND TTW MIND MAPPING STRATEGY IN STRAIGHT LINE EQUATION MATERIAL VIEWED FROM LOGICAL MATHEMATICS INTELLIGENCE - Arif Hardiyanti; Mardiyana Mardiyana; Ikrar Pramudya (Proceedings Education and Language International Conference, 2017)
The purpose of this study was to find out: (1) Which is more effective, TPS Mind Mapping (TPS MM) strategy or Think Talk Write Mind Mapping strategy (TTW MM), (2) Which category of logical mathematic intelligence that can provide better mathematics achievement, (3) In each of the model, which in the categories of logical mathematical intelligence that can provide learning achievement better mathematics learning, logical mathematical intelligence is high, medium or low,(4) In each category of the logical mathematic intelligence ( high, medium,and low ), which is more effective between TPS Mind Mapping strategy and TTW Mind Mapping strategy. This type of research is a quasi experimental with 2×3 factoriall design. The Pupulation on the research is all eighth grade of students junior high schools in Sukoharjo regency in the academic years of 2016/2017. The sample was conducted by using stratified cluster random sampling. The study concluded: (1) TPS Mind Mapping strategy was as effective as TTW Mind Mapping strategy, (2) the students’ learning achievement with high logical mathematic inteligence is better than students achievement with mediumm or low logical mathematic intelligence, while the students’ learning achievement with medium logical mathematic intelligence was better than students’ achievement with low logical mathematic intelligence, (3) in each of the model, the students’ with high logical mathematic inteligence has better than students with medium and low logical mathematic inteligence, and students with logical mathematics intelligence had an equal achievement with low logical mathematic intelligence, (4)on each of category the logical mathematic intelligence, TPS Mind Mapping strategy provides similar outcome with TTW Mind Mapping strategy.Keywords: Think Talk Write, Think Pair Share, Mind Mapping, Logical Mathematic Intelligence